2009
DOI: 10.2337/dc08-1631
|View full text |Cite
|
Sign up to set email alerts
|

Combined Measurement of Fasting Plasma Glucose and A1C Is Effective for the Prediction of Type 2 Diabetes

Abstract: OBJECTIVE -We prospectively assessed whether the combined measurements of fasting plasma glucose (FPG) and A1C were effective for predicting type 2 diabetes.RESEARCH DESIGN AND METHODS -Study participants included 6,736 nondiabetic Japanese men aged 40 -55 years. Type 2 diabetes was diagnosed in those who had an FPG Ն126 mg/dl or who were being treated with an oral antidiabetic agent or insulin. The models including FPG, A1C, and both were compared using the area under the receiver operating characteristic (AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 12 publications
8
94
3
1
Order By: Relevance
“…The model with HbA1c did not provide additional capability to discriminate individuals who developed diabetes from those who did not, although the HbA1c in the clinical model was significantly associated with the incidence of diabetes (P<0.0001). This result differed from the results of Sato et al, 28 who showed that a model including both FPG and HbA1c had a greater AROC than those that included FPG alone. The AROC or cstatistic measure is the most popular method of assessing discriminatory ability, and their interpretation is simple and direct.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The model with HbA1c did not provide additional capability to discriminate individuals who developed diabetes from those who did not, although the HbA1c in the clinical model was significantly associated with the incidence of diabetes (P<0.0001). This result differed from the results of Sato et al, 28 who showed that a model including both FPG and HbA1c had a greater AROC than those that included FPG alone. The AROC or cstatistic measure is the most popular method of assessing discriminatory ability, and their interpretation is simple and direct.…”
Section: Discussioncontrasting
confidence: 57%
“…27 Recently, Sato et al suggested that the combined measurement of FPG and HbA1c was effective for predicting diabetes. 28 They found that both FPG and HbA1c are independently associated with the risk of diabetes. A French cohort study reported the use of HbA1c in identifying subjects with impaired fasting glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The oral glucose tolerance test is rarely used in clinical practice and we define diabetes in this article by either FPG ≥ 7.0 mmol/l and/or HbA1c ≥ 6.5%, as this combination is likely to be used in clinical practice, as proposed in other publications [15,16]. However, we have also included diabetes defined additionally by 2hPG ≥ 11.1 mmol/l, to evaluate possible changes in FPG and HbA1c thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, individuals with moderately elevated HbA1c levels have higher incident rates of T2D over time [49][50][51][52][53][54][55][56][57][58][59][60], supporting the use of HbA1c for risk stratification in the general population. HbA1c is also able to predict future T2D in various nonEuropean populations around the world [9,10,51,[53][54][55][56][57][58][59]61]. In the 1990s, the Diabetes Control and Complications Trial (DCCT) [62] and United Kingdom Prospective Diabetes Study (UKPDS) [63] established clear relationships between HbA1c levels and risk of diabetes-related endpoints in both type 1 diabetes and T2D patients.…”
Section: (B)mentioning
confidence: 99%